Radioguided sentinel lymph node detection in vulvar cancer. Issue 3 (1st April 2005) - Merisio, C.; Berretta, R.; Gualdi, M.; Pultrone, D. C.; Anfuso, S.; Agnese, G.; Aprile, C.; Mereu, L.; Salamano, S.; Tateo, S.; Melpignano, M.
Abstract : Lymph node status is the most important prognostic factor in vulvar cancer. Histologically, sentinel nodes may be representative of the status of the other regional nodes. Identification and histopathologic evaluation of sentinel nodes could then have a significant impact on clinical management and surgery. The aim of this study was to evaluate the feasibility and diagnostic accuracy of sentinel lymph node detection by preoperative lymphoscintigraphy with technetium-99 m–labeled nanocolloid, followed by radioguided intraoperative detection. Nine patients with stage T1, N0, M0, and 11 patients with stage T2, N0, M0 squamous cell carcinoma of the vulva were included in the study. Only three cases had lesions exceeding 3.5 cm in diameter. Sentinel nodes were detected in 100% of cases. A total of 30 inguinofemoral lymphadenectomies were performed, with a mean of 10 surgically removed nodes. Histological examination revealed 17 true negative sentinel nodes, 2 true positive, and 1 false negative. In our case series, sentinel lymph node detection had a 95% diagnostic accuracy, with only one false negative. Based on literature evidence, the sentinel node procedure is feasible and reliable in vulvar cancer; however, the value of sentinel node dissection in the treatment of early-stage vulvar cancer still needs to be confirmed.